Impact of dividend policy on shareholders wealth and firm performance in Pakistan - Khadija Farrukh (Taylor & Francis Group, 2017)
In the field of corporate finance the question as to whether dividend policy affects the shareholders wealth still remains unresolved. The objective of this research paper is to establish the impact of dividend policy on shareholders’ wealth and firm performance in Pakistan. The conduct of dividend policy has been one of the most debatable issues in literature of corporate finance. Numerous researchers have attempted to reveal issues with respect to the dividend policy, however, we still don’t have a worthy explanation regarding the behavior of dividend policy. The variables used in this research are dividend policy, shareholders wealth, and firm performance. Dividend per share and dividend yield are used to measure dividend policy. For shareholders wealth, earning per share and share price are used as proxies. Return on equity is used to measure firm performance. From the regression result, it is found out that dividend policy has positively significant impact on shareholders’ wealth and firm performance. This study supported dividend relevance theory, signaling effect theory, bird in hand theory and clientele-effect theory. The study commends the implementation of stable, effective, managed and target-oriented dividend policy by firm’s financial managers along with effective supervisory framework governed by capital market regulatory bodies to uplift firms’ performance and shareholders wealth in Pakistan. Furthermore, appropriate firm disclosure with respect to dividend payout and dividend per share is needed to guard the potential investors in making the right investment choices in listed firms.